SURFACE STRATEGY TAXONOMY ON FOREIGN LANGUAGE WRITING: A STUDY ON VERB TENSE USAGE - Rusmiati Rusmiati (UNIVERSITAS SERAMBI MEKKAH, 2010)
This study is aimed at analyzing errors of verb tense usage found in the learners’ writing production. The second semester students of English Department, STAIN Gajah Putih Takengon enrolled in Writing II course were taken as the participants in this investigation. Eight narrative paragraphs were scrutinized closely to detect errors pertaining to verb tense. In this case, a classification of errors proposed by Dulay, Burt, and Krashen (1982 in Ellis and Barkhuizen, 2005) called Surface Strategy Taxonomy is applied. It comprises four sorts of errors: addition, omission, misformation, and misordering. The finding reveals that the learners’ errors encompass three types of four aforementioned above, i.e. addition, omission, and misformation. Among those, misformation is found to be the most prevalent type commited by the learners, as many as 62 errors making up 72.94 % of all. It was subsequently followed by omission and addition which were 13 errors (15.29 %) and 10 errors (11.77 %) successively. Whereas misordering was not identified among the learners’ errors on paragraph composition. Eventually, a pedagogical implication as a result of this research was made. English instructors are expected to accentuate more on likely-to-produce-errors items to the learners prior to composing a paragraph.